PENERAPAN TEKNIK WEB SCRAPING UNTUK PENGGALIAN POTENSI PAJAK (STUDI KASUS PADA ONLINE MARKET PLACE TOKOPEDIA, SHOPEE DAN BUKALAPAK) - Mohammad Djufri (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2020)
Currently, millions of transaction data are avaliable on the internet, which can be retrieved and analyzed for excavating potential taxes. This article aims to examine whether the search data through web scraping techniques can be applied in an attempt to excavate the potential tax by the Account Representative. This paper uses an informetric approach, which will be examined quantitative information in the form of transaction data of sellers recorded on the three online marketplace (OMP) namely Tokopedia, Shopee and Bukalapak. The results show that web scraping techniques can be used for extracting potential taxes, and the best web scraping technique that can be done by the Directorate General of Taxation (DJP) is to develop its own integrated web scraping application as a Business Intelligence system. The results of this research are expected to contribute academically in the form of the use of web scraping in data extraction for the excavation of potential taxes and policy implications in terms of data search through the internet by the Directorate General of Taxation